Epoxidation of 2-Styrylchromone derivatives - Santos, Clementina M.M. (2004)
2-Styrylchromones constitute a small group of natural heterocyclic compounds with significant biological properties. Certain natural and synthetic hydroxyl derivatives have shown important pharmacological and mainly antioxidant activities [1 ,2]. We are interested in the design of new 2-styrylchromones analogues containing hydroxyl groups at C-3 and in the Ca=C~ systems because they could increase the antioxidation activity of these type of compounds [2]. Our first approach is the preparation of epoxy systems and then we will try to open the epoxy ring to give the desired hydroxyl derivatives. We studied the epoxidation of 2-styryl-chromones 1 with hydrogen peroxide and iodosylbenzene using [salen Mn(lll)] as catalyst, and the epoxy products 2 were obtained in moderate yields. Since the best results were obtained with iodosylbenzene, we applied oxidant to compounds 3 in order to prepare 4. In this communication, we will report the synthetic details and the structural characterisation of the epoxides 3 and 4.